A protocol for secret key infusion from satellite transmissions - Wahiddin, Mohamed Ridza; Noor Sham, Noor Shamilla Shanaz; Saeb, Magdy M.; Mior Hamdan, Mior Hadi (IJCNS, 2010)
In symmetric encryption systems, secure messages are exchanged with the encrypted message sent over a public channel and the key over a secure channel. Quantum key distribution is an alternative method to share a common key without having to transmit the key. However, it is still in the development stage and possibly proves to be expensive and impractical in the foreseen future. It is useful to have a cheaper and simpler protocol to locally generate the secret key at the sender and receiver locations. In this work, we propose the capturing of bits from an external source such as a radio or a satellite digital transmission to locally generate a mutual key. We introduce a synchronization technique and a framework to ensure that both parties will be receiving the same bit string. The protocol stages include a synchronizing bit-pattern, capturing a bit string and then processing it. The resulting pseudo random bit string is then hashed to provide the required key. The nature of the signal, the vast selection of the timeframe, the downloading sequence, the various source stations and other parameters ensure eavesdropping to be exceedingly unmanageable.